The Influence of Heat Setting Conditions on Mechanical Properties of PTT Filaments (Journal of Fiber Bioengineering and Informatics, 2018)
It is proposed that Poly(Trimethylene Terephthalate) (PTT) filaments are used for fabricating vascularprostheses instead of Poly(Ethylene Terephthalate) (PET) because of their lower Young's modulus andsuperior elastic recovery. The heat setting process is necessary to keep the stability of shape andmechanical properties as well as making the flattened tubular structures round. However, the bestheat setting condition for keeping properties of lower Young's modulus and superior elastic recovery ofPTT filaments is unknown. This paper studies the influence of different heat setting conditions to thechange of Young's modulus and elastic recovery. The temperature range is chosen from 120 to 180 °C and time period is chosen from 30 s to 90 s. The heat setting of yarns is both done in the relaxationstate and tension state. Results show that the best heat setting conditions to get lower modulus, higherelastic recovery and better creep property at the temperature of 160 °C under the tension state through60 s. The tension or relaxation state has the biggest influence on elastic recovery and Young's moduluswhile time period has the least influence.